FACTORS INFLUENCING ACADEMIC PERFORMANCE OF 10TH - 11TH GRADE GIRLS AT CO-EDUCATION PUBLIC SCHOOLS IN SOUTHERN KAZAKHSTAN - Salykova, Aigerim (Nazarbayev University Graduate School of Education, 2024)
Globally, prioritizing girls' education has emerged as a critical focus for nations aiming to boost economic growth and human development. Girls' education has the potential to transform lives, yet substantial obstacles and problems still exist within Kazakhstan and other parts of Central Asia, limiting its full impact. Therefore, the purpose of this study was to examine factors influencing the academic performance of recent 10th and 11th-grade female graduates from public co-educational high schools in the southern part of Kazakhstan by exploring the factors and challenges that girls face as they pursue their academic aspirations. The research questions guiding this study were: how do cultural, societal norms and expectations, socioeconomic and environmental factors influence the academic outcomes of recent female graduates, and what are the policy, practice and research implications of the findings. This qualitative research study utilizes Vygotsky's Sociocultural Theory to gain a broader understanding of inclusivity and gender equity issues within educational settings. Data was collected through in-depth, semi-structured interviews with ten recent female graduates from co-educational public schools in southern Kazakhstan. All participants were 18 years old or older. Interviews were analyzed using thematic analysis approach. The key findings of the study sheds light on the complex interplay of cultural, socioeconomic, and environmental factors influencing the academic performance of female students in Kazakhstan. The study revealed both challenges and motivators for girls' educational success in southern Kazakhstan. High societal expectations for girls to outperform boys academically, coupled with financial concerns, create significant challenges. However, these pressures can also drive motivation and ambition. Supportive school environments, teachers who employ non-discriminatory gender-neutral teaching practices, and the prospect of state scholarships for free higher education all play pivotal roles in shaping positive academic outcomes. The study findings could influence existing laws, regulations, guidelines, and resource allocation by providing a basis for developing gender-sensitive educational policies and practices. At the national level, Kazakhstan could lead in Central Asia by implementing policies that serve as models for gender inclusivity in education. Policies should mitigate societal expectations' pressures on girls and harness societal norms' motivation to promote educational aspirations. This approach aligns with the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 5 (Gender Equality), emphasizing the importance of inclusive and equitable quality education and promoting lifelong learning opportunities for all. Internationally, these findings could contribute to global discussions on gender equality in education, influencing policy-making and decision-making processes to consider the unique cultural, societal, and economic contexts of different regions.
Keywords: Type of access: Restricted; girls’ education; inclusivity; Kazakhstan; Central Asia; gender equity